Study of gene expression alteration in male androgenetic alopecia: evidence of predominant molecular signalling pathways. (25th October 2017) - Michel, L.; Reygagne, P.; Benech, P.; Jean‐Louis, F.; Scalvino, S.; Ly Ka So, S.; Hamidou, Z.; Bianovici, S.; Pouch, J.; Ducos, B.; Bonnet, M.; Bensussan, A.; et al.
Summary: Background: Male androgenetic alopecia (AGA) is the most common form of hair loss in men. It is characterized by a distinct pattern of progressive hair loss starting from the frontal area and the vertex of the scalp. Although several genetic risk loci have been identified, relevant genes for AGA remain to be defined. Objectives: To identify biomarkers associated with AGA. Methods: Molecular biomarkers associated with premature AGA were identified through gene expression analysis using cDNA generated from scalp vertex biopsies of hairless or bald men with premature AGA, and healthy volunteers. Results: This monocentric study reveals that genes encoding mast cell granule enzymes, inflammatory mediators and immunoglobulin‐associated immune mediators were significantly overexpressed in AGA. In contrast, underexpressed genes appear to be associated with the Wnt/β‐catenin and bone morphogenic protein/transforming growth factor‐β signalling pathways. Although involvement of these pathways in hair follicle regeneration is well described, functional interpretation of the transcriptomic data highlights different events that account for their inhibition. In particular, one of these events depends on the dysregulated expression of proopiomelanocortin, as confirmed by polymerase chain reaction and immunohistochemistry. In addition, lower expression of CYP27B1 in patients with AGA supports the notion that changes in vitamin D metabolism contributes to hair loss. Conclusions: This study provides compelling evidence for distinct molecular events contributing to alopecia that may pave the way for new therapeutic approaches. Abstract : What's already known about this topic? Male androgenetic alopecia (AGA) is the most common type of baldness, characterized by progressive patterned hair loss from the scalp. It is hereditary in > 80% of cases, although the inheritance of male AGA is not fully understood. The process is highly influenced by the androgens, with an inhibitory role of the metabolite 5‐α‐dihydrotestosterone, and a reciprocal relationship between activated Wnt/β‐catenin and androgen receptor signalling within the hair follicles. What does this study add? This study examines biomarkers associated with AGA through gene expression analysis of scalp biopsies from 14 young (age < 35 years) patients with AGA compared with young healthy male volunteers. Functions of the genes differentially expressed in the patients with AGA were depicted and integrated within functional molecular networks of known relevance in hair cycle regulation. What is the translational message? Specific molecular pathways discriminate patients with AGA from controls. Distinct altered mechanisms converging to inhibit Wnt/β‐catenin signalling account for AGA in young male patients. Reduced β‐catenin activity might be linked to the decreased expression of proopiomelanocortin, bone morphogenic protein 2 and integrin β6, impacting negatively on the transcriptional activity of transforming growth factor‐β. Altered vitamin D metabolism with reduced calcitriol production was shown, as well as evidence of B‐ and T‐cell involvement, suggesting an underlying autoimmune‐related mechanism. Linked Comment: Chew. Br J Dermatol 2017; 177 :1159–1160 . Respond to this article